2018
DOI: 10.1097/mat.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Biventricular Epicardial Augmentation Technology in a Drug-Induced Porcine Failing Heart Model

Abstract: For treatment of advanced heart failure, current strategies include cardiac transplantation or blood-contacting pump technology associated with complications, including stroke and bleeding. This study investigated an individualized biventricular epicardial augmentation technology in a drug-induced porcine failing heart model. A total of 11 pigs were used, for the assessment of hemodynamics and cardiac function under various conditions of support pressures and support durations (n = 4), to assess device positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The aim was to investigate the short‐term influence, impact, and function of the novel BiVAD prototypes on pharmacologically induced failing heart models in order to provide proof of concept and extract valuable indices of heart assistance to promote further developments in the field of this novel VAD technology. Particulars of the in vivo animal study are described in the previous study …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The aim was to investigate the short‐term influence, impact, and function of the novel BiVAD prototypes on pharmacologically induced failing heart models in order to provide proof of concept and extract valuable indices of heart assistance to promote further developments in the field of this novel VAD technology. Particulars of the in vivo animal study are described in the previous study …”
Section: Methodsmentioning
confidence: 99%
“…A regression‐based statistical model was used in the existing study to evaluate whether BiVAD treatment has significant influence on cardiac function parameters for these two heart failure models. The analysis revealed that increasing left ventricular augmentation pressure significantly increased stroke volume and systolic pressures and lowered end‐diastolic pressure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations